Evaluation of Extracranial Carotid Arteries in Ischemic Stroke Patients Using Color Doppler Sonography and Correlation with Various Risk Factors - Pathak, Manish Raj; Gautam, Mahesh; Pathak, Yagya Raj (Journal of Nobel Medical College, 2019)
Background: Cerebral ischemic stroke is the major cause of death after ischemic heart disease and malignancies, among which major cases of stroke results from atherosclerosis of intra and extra-cranial carotid vessels. The aim of this study is to evaluate the extracranial carotid arteries in patients with ischemic stroke and correlation with various risk factors. Materials and Methods: A cross sectional study of the patients with ischemic stroke presented in Radiology department of Nobel Medical College were evaluated for a period of one year from February 2017- January 2018 using color Doppler ultrasound and correlated with various risk factors. A total of 50 patients were included in the study. All age groups and sex were included. Results: Out of 50 patients, 29 patients (58%) were males and 21 patients (42%) were females. Stroke was present in 24 patients on right side and 26 patients on left side. A total of 36 patients had extra-cranial carotid stenosis. Among them, 18 patients had <50% stenosis, 17 patients had >50% stenosis and 1 patient had complete occlusion. The most common cause of obstruction was found to be atherosclerotic changes in the form of atheromatous plaque. Out of 50 patients 27 had history of hypertension and 19 had history of smoking. Out of 27 hypertensive patients, 23 had stenosis which is statistically significant (p value 0.024). Conclusion: The current study shows the importance of color Doppler ultrasound as an economic, safe and non-invasive method of demonstrating the cause of stroke in extra-cranial carotid artery system